A Case of Critical Aortic Stenosis Masquerading as Acute Coronary Syndrome. (20th July 2010) - Wayangankar, Siddharth A.; Dasari, Tarun W.; Lozano, Pedro M.; Beckman, Karen J.
Abstract : Serum cardiac troponins I and T are reliable and highly specific markers of myocardial injury. Studies have shown that at least 20% of patients with severe aortic stenosis have detectable serum troponins. This case report describes a patient who presented as suspected acute coronary syndrome with markedly elevated troponin levels, who was later found to have normal coronaries and critical aortic stenosis. This case highlights the need for comprehensive and accurate physical examination in patients who present with angina. Critical aortic stenosis may cause such severe subendocardial ischemia as to cause marked elevation in cardiac markers and mimic an acute coronary syndrome. Careful physical examination will lead to an earlier use of non invasive techniques, such as echocardiography to confirm the correct diagnosis and the avoidance of inappropriate treatments such as intravenous nitroglycerin and glycoprotein IIb/IIIa inhibitors.